Orientation polarization from faster motions in the ultraviscous and glassy diethyl phthalate and its entropy - VIJ, JAGDISH (My University, 2006)
Dielectric spectra of the relaxation in glassy and ultraviscous liquid diethyl phthalate show that its relaxation strength , the distribution of times, and the relaxation rate are more sensitive to temperature T in the ultraviscous liquid than in the glassy state. The against temperature plot has an elbow-shaped break near Tg of ~181 K, which is remarkably similar to that observed in the entropy, enthalpy, and volume against temperature plots, and in the plot of against the liquid's entropy minus its 0 K value. The ratio of to diethyl phthalate's entropy, after subtracting the 0 K value, is 1.08?10?3 mol K/J in the glassy state at 120.4 K, which decreases slowly to 0.81?10?3 mol K/J at 176 K near Tg and thereafter rapidly increases to 1.57?10?3 mol K/J at 190 K. Variation in parallels the variation of the entropy. A change in the activation energy of the process at T>Tg indicates that its rate is also determined by the structure of the ultraviscous liquid. Features of relaxation are consistent with localized motions of molecules and may not involve small-angle motions of all molecules
PUBLISHED
Article Number: 044513
Keywords: Electronic & Electrical Engineering